HERMENEUTICS OF HADITH IN THE SUFI TRADITION: ANALYSIS THE CONCEPT OF HADITH INTERPRETATION AMONG THE SUFIS - Muhammad Isnaini; Romlah Abu Bakar Askar; Abdul Ghofur (PT. Jurnal Center Indonesia Publisher, 2025)
This research article aims to analyze the methods of Hadith interpretation employed within the Sufi tradition. This study examines various hermeneutical approaches applied by Sufis, including esoteric interpretation, the role of spiritual intuition (kashf), the use of analogy and metaphor, and the influence of Sufi order (tariqa) teachings and practices. The article also highlights figures such as Al-Qushayri, Al-Tirmidhi, Ibn Arabi, Al-Ghazali, Junayd al-Baghdadi, and Abu 'Abd al-Rahman al-Sulami, as well as major Sufi orders like Chishti and Qadiri. Through an analysis of examples of Hadith interpretations, this research demonstrates the significance and unique contribution of Sufi Hadith hermeneutics to the understanding of Islamic spirituality, while also identifying contemporary issues and academic debates related to these methods. The conclusion of this research underscores the richness and complexity of Hadith hermeneutics within the Sufi tradition, as well as its relevance in the broader context of Islamic studies.